Apigenin Alleviates Obesity-Associated Metabolic Syndrome by Regulating the Composition of the Gut Microbiome - Qiao, Yuan; Zhang, Zhichun; Zhai, Yuanyuan; Yan, Xu; Zhou, Wenling; Liu, Hao; Guan, Lingling; Peng, Liang (Frontiers in Microbiology, 2022)
The gut microbiota, often viewed as a “digestive organ”, can influence the development of obesity and related metabolic disorders. Diet is of important significance in shaping the structure and modulating the function of the gut microbiota. Apigenin (Api) widely exists in fruits and vegetables as a naturally occurring flavonoid and has anti-obesogenic, anti-inflammatory, and anti-carcinogenic properties. Its low bioavailability means it has enough time to interact with the intestine and thus becomes a potential substrate for the gut microbiota, thereby contributing to gut health. Here we show that Api reduces whole-body weight, low-grade inflammation, and insulin resistance in high-fat diet (HFD)-induced obese mice. Our results reflect that Api supplementation can substantially improve intestinal dysbiosis triggered by HFD and also restores gut barrier damage by alleviating metabolic endotoxemia. Augmentation of Akkermansia and Incertae_Sedis along with reduction of Faecalibaculum and Dubosiella at the genus level potentially mediated the protective effects of Api on metabolic syndrome. Furthermore, we show that the impact of Api on the reduction of body weight and the modification of gut microbiota could be transferred from Api-administered mice to HFD-feeding mice via horizontal fecal microbiota transplantation. Taken together, our data highlight the prebiotic role of Api and show its contribution to the restraint of gut dysbiosis and metabolic deterioration associated with obesity in mice.